MAJA GŁOWACKA, MONIKA HELAK, MAŁGORZATA ŁUKIANOW, JUSTYNA ORCHOWSKA, MATEUSZ MAZZINI, Pamiętniki pandemii - Gałek, Michał (LUD. Organ Polskiego Towarzystwa Ludoznawczego, 2023)
Tekst stanowi recenzję książki "Pamiętniki pandemii"